Pengaruh Lokasi, Kualitas Layanan Dan Promosi Terhadap Loyalitas Pelangan Di Vena Veni Mart Sungai Geringging - Reflianto, Reflianto; Rahayu, Sari; Amra, Ikbal; Nini, Nini (Jurnal Pustaka Manajemen (Pusat Akses Kajian Manajemen), 2023)
The background of this research is to measure the influence of location, service quality and promotion on customer loyalty at Vena Veni Mart Sungai Gertingging. This research is a survey research obtained based on distributing questionnaires. The population in this research is customers of Vena Veni Mart Sungai Geringging. The sample used in This research consisted of 70 respondents, using accidental sampling techniques, the data was processed with SPSS 23.0. The results of the research can be concluded; 1) Location influences customer loyalty at Vena Veni Mart Sungai Geringging; 2) Service quality influences customer loyalty at Vena Veni Mart Sungai Geringging; 3) Promotion influences customer loyalty at the Vena Veni Mart Sungai Geringging and 4) Location, service quality and promotion together influence customer loyalty at the Vena Veni Mart Sungai Geringging with a regression coefficient Y= 0.952+0.204X1+0.314X2+0.204 X3 with R = 0.577 or R2 = 0.333. Location, service quality and promotions influence customer loyalty by 33.3%, while the remaining 66.7% are influenced by other variables outside of the variables of this research; The suggestions in this research are: 1) For the Vena Veni Mart location in Geringging River, it is necessary to expand the parking area; 2) For product prices at Veni Mart, it is best to give discounts to loyal customers so that these customers do not move to other places; 3) For promotions, you must provide a variety of products so that customers' buying interest increases.